The effects of women board directors on firm performance: An empirical evidence from Malaysia - Nurul Farhana, Ahmad Sabri (2013)
Gender diversity in boardroom has been associated with corporate governance and firm performance and it’s had become one of the focuses of the related study. This study examines the effects of women on the board of directors to firm performance (ROA and Tobin’s Q) for the data set of 80 listed companies in Bursa Malaysia on year 2011 and employs Multiple Regression Analysis for the regression test. This thesis investigates the relationship between women on board of directors and firm performance which is examines roles of proportions of women on board of directors, women director in audit committee and independent women director on the board in constraining the firm performance. In general, this study contributes to the literature by testing the issue of women on the board of directors and investigates major women factors are related to the performance of the companies and it aims to provide empirical evidence according to regulatory and business environments in Malaysia. This study founds a negative relationship between proportion of women on the board of directors and independent women director on the board to the firm performance (ROA and Tobin’s Q), results also indicates that women in audit committee has a positive relationship to firm performance (ROA and Tobin’s Q).